2010
DOI: 10.1258/ebm.2010.010124
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of the antibreast carcinoma cell growth components of Vernonia amygdalina extracts

Abstract: Vernonia amygdalina (VA) is widely used for medicinal and food purposes in tropical Africa. Many health benefits (antioxidant, antimicrobial, anticancer activities and more) of VA extracts have been reported. The mechanisms of actions have also been described. We have previously reported that VA extracts elicited growth inhibitory activities in human estrogen receptor-positive (ER(+)) cells (MCF-7 cells) and ductal carcinoma cells (BT-549) in vitro. The active components in the organic solvent (chloroform)-ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Over the years, several studies on the chemical components of this species, including flavonoids [ 2 ], sesquiterpene lactones [ 3 ], steroidal saponins [ 4 , 5 , 6 ], and fatty acids [ 7 ], have been performed. Previous studies have indicated different bioactivities of this species, including anti-inflammation [ 8 ], anti-malaria [ 9 ], anti-obesity [ 10 , 11 ], antioxidant [ 12 , 13 ], anti-tumor [ 14 ], and other activities [ 15 ]. Water and chloroform extracts of V. amygdalina (VA) interfere with the DNA synthesis of MCF-7 cells in breast cancer, affecting the activity of ERKs in vitro and inhibiting human breast cancer cells [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, several studies on the chemical components of this species, including flavonoids [ 2 ], sesquiterpene lactones [ 3 ], steroidal saponins [ 4 , 5 , 6 ], and fatty acids [ 7 ], have been performed. Previous studies have indicated different bioactivities of this species, including anti-inflammation [ 8 ], anti-malaria [ 9 ], anti-obesity [ 10 , 11 ], antioxidant [ 12 , 13 ], anti-tumor [ 14 ], and other activities [ 15 ]. Water and chloroform extracts of V. amygdalina (VA) interfere with the DNA synthesis of MCF-7 cells in breast cancer, affecting the activity of ERKs in vitro and inhibiting human breast cancer cells [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Via the MTT method, it has been verified that MCF-7 cells are inhibited in vitro and the DNA synthesis of BT-549 cells in breast cancer is disturbed by the addition of VA extract [ 18 , 19 ]. Moreover, three active fractions extracted from ethanol extracts of V. amygdalina have an inhibiting effect on tumor cells, the essential component being steroidal saponins [ 14 ]. So far, a certain amount of steroidal saponins has been obtained from V. amygdalina; however, studies on the anti-tumor activity are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Plants native to Nigeria have also been shown to possess anticoccidial activity (Nweze and Obiwulu, 2009). Nigeria herbal plants Vernonia amygdalina (VA) and Azadirachta indica (AI) have been considered potentially effective chemo-preventive and chemotherapeutic agents against breast cancer cells (Luo et al, 2010;Kumar et al, 2009). V. amygdalina was reported to have an anthelmintic and hepatoprotective properties (Adedapo et al, 2007;Adesanoye and Farombi, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Table S10, Supporting Information , summarizes the use of CCS to prepare fractions for bioassay screening of natural products in articles published since 2007. 20 , 35 , 41 , 44 , 74 , 94 , 102 , 105 , 116 , 122 , 128 , 135 137 , 139 , 229 , 230 , 279 , 284 , 285 , 295 , 298 , 307 , 308 , 324 – 326 , 344 , 345 , 359 402 …”
Section: Bioactivity and Nonplant Applicationsmentioning
confidence: 99%